Predictive Modelling of Health Risks Using Logistic Regression for Personalized Dietary Recommendations (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The prevalence of diet-related chronic diseases such as Type 2 Diabetes Mellitus (T2DM) and hypertension necessitates the development of intelligent nutritional systems that go beyond user preference to prioritize clinical safety. Traditional food recommender systems often suffer from a "health-blind" bias, optimizing primarily for taste or popularity. This paper proposes a novel Risk-Aware Diet Recommendation System (RADRS) that integrates Logistic Regression (LR) for interpretable health risk assessment with Linear Programming (LP) for dietary optimization. By training LR models on the NHANES and Pima Indians Diabetes datasets, the system calculates individual disease probabilities. These probabilities dynamically configure nutritional constraints—specifically modifying sodium, carbohydrate, and saturated fat limits—within an LP solver. The proposed architecture bridges the gap between predictive health analytics and personalized meal planning, ensuring that recommendations are both palatable and medically compliant. Keywords—Health Informatics, Logistic Regression, Recommender Systems, Linear Programming, Personalized Nutrition, Chronic Disease Management.